The Implementation of Good Corporate Governance (GCG) Principles Over Goods & Services Procurement Over PT. Angkasa Pura Solusi - Qisthina Izazi Shaleha; Suyud Margono Shaleha (Journal of Multidisciplinary Academic, 2021)
The principles in Good Corporate Governance (GCG) have been applied at PT. Angkasa Pura Solusi as a subsidiary of State-owned enterprises of Indonesia (BUMN). This activity has referred to Article 3 PER-01/ MBU/2011 issued by the State Minister for BUMN concerning the Implementation of Good Corporate Governance. As a BUMN which consists of transparency, accountability, independence, responsibility and fairness. Theoretically, the practice of the principles of Good Corporate Governance in BUMN holding can increase the value (valuation) of the company by increasing the performance and value of the company so that it can benefit state revenues in the form of dividends, taxes, employment, and competitive products and services to consumers. The legal basis for the procurement of goods and services in BUMN is based on the Regulation of the Minister of BUMN No.PER-05 / MBU / 2008 concerning General Guidelines for the Implementation of the Procurement of Goods and Services for State-Owned Enterprises. This specificity is enforced because BUMN is a form of business entity which all or most of its capital is owned by the state through direct participation originating from separated state assets. Thus, the enactment of the Regulation of the Minister of BUMN Number PER-05 / MBU / 2008, the Board of Directors of PT. Angkasa Pura Solusi has established Guidelines for the Procurement of Goods and Services based on the Decree of the Board of Directors Number: 013B / APS / SK / DIR / III / 2018, dated March 26, 2018 regarding Barag Procurement Guidelines / Services PT. Angkasa Pura Solusi. This regulation regulates the mechanism for the procurement of goods and services at PT. Angkasa Pura Solusi. In every process of procuring goods and services at PT. Angkasa Pura Solusi, it must refer to this regulation.